2019
DOI: 10.1111/jopr.13072
|View full text |Cite
|
Sign up to set email alerts
|

Bias: A 30‐Year Review of Randomized Controlled Trials Published in Three Prosthodontic Journals

Abstract: Purpose Bias can occur in various phases of an investigation, and its control is an important measure of the validity of results for randomized controlled trials (RCTs). The purpose of this study is to determine if bias control in prosthodontic RCTs published from 2008 to 2017 improved over those published from 1988 to 1997. Materials and Methods MEDLINE was searched for RCTs in The International Journal of Prosthodontics, The Journal of Prosthetic Dentistry, and The Journal of Prosthodontics published from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Saltaji et al (2017) reported that the implementation of randomization and blinding dental trials overall improved significantly over time (1955 to 2013). Improvements were also reported in orthodontics (Koletsi et al 2017) and over 30 y in prosthodontics (Dumbrigue, et al 2019a). Both design issues are integral to rigorous clinical trials and in reaching meaningful and trustworthy findings.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Saltaji et al (2017) reported that the implementation of randomization and blinding dental trials overall improved significantly over time (1955 to 2013). Improvements were also reported in orthodontics (Koletsi et al 2017) and over 30 y in prosthodontics (Dumbrigue, et al 2019a). Both design issues are integral to rigorous clinical trials and in reaching meaningful and trustworthy findings.…”
Section: Discussionmentioning
confidence: 91%
“…Despite improvements over time (Dumbrigue et al 2019a), specific issues included use of inappropriate and/or unclear methods of randomization and lack of blinding (Table 2). Adequacy of randomization ranged from 9% to 68% (Appendix Fig.…”
Section: Resultsmentioning
confidence: 99%